Coloproctology : A Practical Guide - Beynon, John; Harris, Dean Anthony; Davies, Mark; Evans, Martyn (Springer International Publishing : Imprint: Springer, 2017)
The topics covered in this book have been specifically chosen to give guidance to surgeons established in practice and those embarking on their careers. Examples include the changing management in the treatment of the catastrophic abdominal wall, perianal Crohn's disease in the biological era, decision making in rectal cancer that responds to radiotherapy, and the assessment of outcomes in colorectal cancer surgery. Recent years have seen the introduction of technical advances with respect to robotics in colorectal surgery and trans-anal total meso-rectal excision, and which are rapidly becoming established in clinical practice. Chapters also cover those aspects of colorectal practice, which are common to all, and provide guidance on management of topics including complications of radiotherapy, management of pouch dysfunction and iatrogenic complications in pelvic cancer surgery.
Keywords: Medicine.; Gastroenterology.; Rectum -- Surgery.; Minimally invasive surgery.; Urology.; elektronické knihy; electronic books